Bamboo as an alternative to batik blocks in the production of batik pattern design aesthetics / Hamdan Lias ... [et al.] - Lias, Hamdan; Azmin, Mohamad Afham; Hasbullah, Sarah Wahidah; Yazmeen, Hana (2024)
In Malaysia, there are 59 species of bamboo from 7 genera. This plant can be an alternative to the existing batik blocks to create patterns with their own aesthetic value. The middle part and cross-sections of the vascular section of the bamboo stem structure spread throughout the trunk contribute to its own aesthetic value in batik pattern design. The study used two types of bamboo as batik blocks, Bambusa blumeana (bamboo thorns) and Gigantocha albociliata (honey bamboo). The focus of the study was to evaluate the aesthetics of the design pattern produced through both types of bamboo as a batik tool. For the study, the researchers used the theory of formalism by Clive Bell (1914/2014) and Roger Fry (1920/2011). The theory of formalism is based on the opinion that the formal aesthetic characteristics relied on the elements and principles of the art design in the bamboo stem structure that are determined by lines, appearance, texture, and diversity arranged in various ways to produce a balanced, orderly and harmonious design during the batik process. The results showed that bamboo as a batik block and its ties can produce a more interesting batik pattern design. Thus, this study serves as an artistic identity and determines the various designs of known textile patterns.